2022
DOI: 10.1007/s11606-022-07827-4
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspectives on the Shift to Telemedicine in Primary and Behavioral Health Care during the COVID-19 Pandemic

Abstract: Background Studies specifically focused on patients’ perspectives on telemedicine visits in primary and behavioral health care are fairly limited and have often focused on highly selected populations or used overall satisfaction surveys. Objective To examine patient perspectives on the shift to telemedicine, the remote delivery of health care via the use of electronic information and communications technology, in primary and behavioral health care in Federally Qualified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A major benefit of video-enabled telehealth is its potential to promote continuity of care . Validity testing revealed that higher scores on the VVUE were associated with both better health care engagement and increased likelihood of continued video visit use in the 6 months after completing the VVUE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A major benefit of video-enabled telehealth is its potential to promote continuity of care . Validity testing revealed that higher scores on the VVUE were associated with both better health care engagement and increased likelihood of continued video visit use in the 6 months after completing the VVUE.…”
Section: Discussionmentioning
confidence: 99%
“…23,31 A major benefit of video-enabled telehealth is its potential to promote continuity of care. 10,46 Validity testing revealed that higher scores on the VVUE were associated with both better health care engagement and increased likelihood of continued video visit use in the 6 months after completing the VVUE. These findings are especially notable because VVUE scores demonstrated incremental validity to factors previously found to be associated with video visit utilization, including health status, the presence of chronic conditions, and demographic characteristics, such as race and ethnicity and age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The insights provided by the analysis of the reviewed articles are numerous. A first fundamental point seems to be the importance that is universally recognized to digital literacy as the key to ensuring an equitable distribution of health services in the society of the third millennium, permeated by digitization and technologization ( 16 , 20 , 27 29 , 33 , 35 , 37 , 47 , 50 ). In order for it to succeed, it is essential that the promotion of digital literacy should not be a temporary and circumscribed measure, but on the contrary should take on a structural character and be explored at all levels of the organization of society ( 21 ).…”
Section: Discussionmentioning
confidence: 99%